Cryptocellus armasi, a new troglomorphic hooded tick-spider from Venezuela (Arachnida, Ricinulei) - Botero-Trujillo, Ricardo; Prendini, Lorenzo (Zootaxa, 2025)
Ricinulei Thorell, 1876, or hooded tick-spiders, are among the least known arachnid orders. Represented by 88 species in the New World and 33 species in South America, only two ricinuleid species have been recorded from Venezuela, one of the Neotropical countries with the least known Ricinulei fauna. In the present contribution, Cryptocellus armasi sp. nov. is described and illustrated from male and female specimens collected inside Cueva de Toromo, a cave in the foothills of the Sierra de Perijá, in the state of Zulia, northwestern Venezuela. The new species, which belongs to the magnus species group, exhibits pronounced attenuation of the appendages. Based on this troglomorphism and hypogean habitat, the new species appears to be a troglobite, the first of its kind in Cryptocellus Westwood, 1874 and the first troglobitic ricinuleid from South America. This new species raises the number of extant ricinuleid species to 103 and the species of Cryptocellus, to 46. Thirty-four of these occur in South America and three in Venezuela. A map plotting the known distributions of the three Venezuelan species of Ricinulei is presented.